2009
DOI: 10.3109/15360280903324127
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Controlled Substance Agreements from Private Practice Physicians

Abstract: Controlled substance management agreements (contracts) are widely used by pain specialists in the United States, but what do they contain? This survey analysis answers that question by taking a thorough look at 41 controlled substance medication management agreements from physicians in private practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Patients would like information on side effects, drug interactions, addiction potential, privacy of the PPA and drug testing. However, a recent analysis of 41 PPAs from 18 states reported that while 98% of the PPAs stipulated the one doctor rule, only 83% contained information on adverse/side effects, 53% contained information about goals of treatment and 34% contained information on drug–alcohol or drug–drug interactions [16]…”
Section: Discussionmentioning
confidence: 99%
“…Patients would like information on side effects, drug interactions, addiction potential, privacy of the PPA and drug testing. However, a recent analysis of 41 PPAs from 18 states reported that while 98% of the PPAs stipulated the one doctor rule, only 83% contained information on adverse/side effects, 53% contained information about goals of treatment and 34% contained information on drug–alcohol or drug–drug interactions [16]…”
Section: Discussionmentioning
confidence: 99%
“…Pain clinicians often require patients to sign a "controlled substance agreement" in order to receive opioid therapy (8). A controlled substance agreement is a written document that contains information about medication risks and side effects, lists instructions for obtaining refills, establishes rules for compliance, and discusses penalties for violations (9). A majority of agreements contain a stipulation requiring patients to consent to random drug screens (9,10) that search for licit and illicit drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Opioids are considered controlled substances (12) and clinicians often have their patients sign a controlled substance agreement (CSA) as a condition of receiving opioid therapy (13). A "controlled substance agreement" is a written document that contains information about medication risks and side effects, lists instructions for obtaining refills, establishes rules for compliance, and discusses penalties for violations (14). Many also provide for consent to opioid therapy and drug testing, and patients are required to sign the agreements (15).…”
Section: Introductionmentioning
confidence: 99%